A percepção de suporte organizacional dos novos servidores da Universidade Federal do Rio Grande do Norte - Oliveira, Alessandra Silva de (2006)
This work deals with organizational support perception-OSP. This is done considering staff global beliefs, value of their contributions, care and well being related of individuals in an organization. These issues has been have been present in many researches since the 80s. It is important to analyze this matter considering all the changes that occurred nationally and internationally in the academic environment, characterized as being diversified in academic and managerial level. This occurs especially in Brazil since Federal Universities and their agents have suffered impact and restructuring. The research has emphasized the technical-managerial as well as professor staff level at Universidade Federal do Rio Grande do Norte aiming to deal with their unsatisfaction upon social political support. Thus, there was participation of 259 staff that were admitted from 2003 to 2005 in many sectors and units of the university. These subjects were submitted to a social and demographical query through an application of a scale of organizational support perception-OSP. Descriptive and multivariate analysis was done considering factors (management style of higher command), material support, wages, work overload, social support at work and ascending levels). Results show that there a hierarchy of the analyzed factors, the factor social support at work as being the first one with 3,31%, the factor management style of the higher command in second with 3,30%, then followed by the factor social support at work with 2,92%, in a sequence the factor material support, factor overload with 2,49% in the fourth position, and in the fifth place, the factor ascending with an average of 2,33% and in last the factor wages with 2,20%. It is concluded that the factors related to the more positive attributions of the OSP (social support at work), in a sequence material support opposing from the most negative factors of the OSP (wages, overload, ascending) reveal a reality that points out that the OSP is very much related to the individualized actions of the members of the organization (leader-member-group) rather than on structure and institutionalized actions carried out at UFRN